More Favorable Palmitic Acid Over Palmitoleic Acid Modification of Wnt3 Ensures Its Localization and Activity in Plasma Membrane Domains - Azbazdar, Yagmur; Ozalp, Ozgun; Sezgin, Erdinc; Veerapathiran, Sapthaswaran; Duncan, Anna L.; Sansom, Mark S. P.; Eggeling, Christian; Wohland, Thorsten; Karaca, Ezgi; Ozhan, Gunes (Frontiers in Cell and Developmental Biology, 2019)
While the lateral organization of plasma membrane components has been shown to control binding of Wnt ligands to their receptors preferentially in the ordered membrane domains, the role of posttranslational lipid modification of Wnt on this selective binding is unknown. Here, we identify that the canonical Wnt is presumably acylated by palmitic acid, a saturated 16-carbon fatty acid, at a conserved serine residue. Acylation of Wnt3 is dispensable for its secretion and binding to Fz8 while it is essential for Wnt3’s proper binding and domain-like diffusion in the ordered membrane domains. We further unravel that non-palmitoylated Wnt3 is unable to activate Wnt/β-catenin signaling either in zebrafish embryos or in mammalian cells. Based on these results, we propose that the lipidation of canonical Wnt, presumably by a saturated fatty acid, determines its competence in interacting with the receptors in the appropriate domains of the plasma membrane, ultimately keeping the signaling activity under control.